Submission to CAC - Kvackaj, Peter; Baronak, Ivan (Communications - Scientific letters of the University of Zilina, 2004)
Asynchronous transfer mode (ATM) is the base for future telecommunication network. The greatly variable requirements for different applications, especially in video and data traffic, make high demands on the development of traffic control in ATM networks. Speaking about Quality of Service (QoS), in ATM there is a traffic control mechanism, which ensures the standard requested by a new application or service. In the following paper an introduction to traffic control mechanism in ATM known as a connection admission control (CAC) and appropriate CAC method are presented.